Iot Based Smart Agriculture Field Monitoring and Control System - Prakashrao, Y.; Rudramurthy, C.; Reddy, P Jyothi Prakash; Devi, Jollu Jyothsna (International Journal of Psychosocial Rehabilitation, 2025)
Mostly in India, the people depend on Agriculture because it is the pillar. The growth of agriculture enhances the productivity of the plantation systems. For irrigation, water is a more precious resource. Normally the usage of water requires an hour. For productive irrigation as well as to save water, better use of soil moisture sensors, gets better plant yields, reduces dependency on fertilizers and improves crop quality. Various methods applied to help the farmer, but it gives less accurate crop production decisions, and makes slower. In the irrigation fields, it is necessary to continuously monitor the soil moisture content for successful irrigation. For smart farming, an IoT – based system is designed for monitoring the crop field with the help of soil moisture sensor and automating the irrigation system. The farmers can monitor the state of the field from anywhere at any moment. Therefore, an IoT-based smart farming is highly efficient when compared to the conventional approach.